Budaya Suku Bugis Sebagai Daya Tarik Wisata Di Pantai Bung Jabe Karimunjawa - Citra Unik Mayasari (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2017)
Indonesia is consist of several islands and have various ethnic, tribal and cultural, so it has great potential in the world of tourism especially cultural tourism. Almost all islands or regions of Indonesia have a culture that can be used as a tourist attraction. One of them is the culture of Bugis tribe used as a tourist attraction in Bunga Jabe Karimunjawa. The manager of Bunga Jabe Karimunjawa currently does the development of tourist attraction by carrying the theme of Bugis tribal culture as a tourist attraction and also as the way to preserve the culture of Bugis tribe on Bunga Jabe Karimunjawa. In this research, researchers used qualitative naturalistic methods because in this study conducted on natural conditions and researchers as the key instrument. Data collection techniques use observation, interview and documentation techniques. Some cultures of Bugis tribe used as a tourist attraction at Bunga Jabe Karimunjawa beach are local language or Bugis language, Bugis traditional art of Pencak Silat Baruga and Paduppa Dance, custom homes of Bugis tribe or stilt house, dwarf house as accommodation and Bugis typical food